2016
DOI: 10.1590/s1983-41952016000600005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wind in the design of reinforced concrete buildings

Abstract: ResumoThis paper presents the results from a parametric study carried in order to quantify how far errors in the design stage related to the consideration of the wind action may put at risk the response and safety of reinforced concrete buildings. Using an architectural model as reference and varying the number of floors of the building, the structural safety was evaluated as a function of the wind action intensity. Results showed that even for low-rise buildings, with 10 floors, ignoring the wind action can s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Although this variable was less studied than air temperature or precipitation, the understanding of the SWS evolution is of great relevance for both productive activities and ecological preservation. Changes in WS regimes are important for coastal erosion (Dragani et al ., 2013; Knorr, 2013), air pollution potential (Gassmann and Mazzeo, 2000), forest and community infrastructure protection (Jungo et al ., 2002), surface energy balance (Rayner, 2007), building construction (Cechet and Sanabria, 2010; Cechet and Sanabria, 2012; Tapajós et al ., 2016), maritime activities (Caires and Sterl, 2005), and wind energy production (Barros, 1983; McVicar et al ., 2008; Cross et al ., 2015). Another important activity for which changes in SWS has a great impact is agriculture production, since it is a driver of evapotranspiration in agricultural systems (de la Casa and Ovando, 2016; Liuzzo et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although this variable was less studied than air temperature or precipitation, the understanding of the SWS evolution is of great relevance for both productive activities and ecological preservation. Changes in WS regimes are important for coastal erosion (Dragani et al ., 2013; Knorr, 2013), air pollution potential (Gassmann and Mazzeo, 2000), forest and community infrastructure protection (Jungo et al ., 2002), surface energy balance (Rayner, 2007), building construction (Cechet and Sanabria, 2010; Cechet and Sanabria, 2012; Tapajós et al ., 2016), maritime activities (Caires and Sterl, 2005), and wind energy production (Barros, 1983; McVicar et al ., 2008; Cross et al ., 2015). Another important activity for which changes in SWS has a great impact is agriculture production, since it is a driver of evapotranspiration in agricultural systems (de la Casa and Ovando, 2016; Liuzzo et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Na literatura são relatados vários exemplos nos quais a ação do vento é apontada como a causa de inúmeros acidentes estruturais (SHA; MALINOV, 2014;MIANG et al, 2016;SOLARI, 2019). Nesse caso, o colapso progressivo é um mecanismo de ruína parcial ou total de uma estrutura provocado pela falha localizada de um elemento estrutural primário levando à redistribuição das cargas para os elementos do entorno, os quais também podem vir a ruir (TAPAJOS et al, 2016).…”
Section: Construção Inadequadaunclassified
“…For example, January 2011, a residential building called Real Class, with 13,400 m² area and about 105 m high, which was under construction in the city of in the city of Belem, Para, Brazil collapsed during a heavy rain, where intense winds were registered in the city. After different studies carried out about the case, it was showed that the wind load was not properly considered in the design [46]. Most wind damage to buildings occurs during strong winds, the high-rise buildings are built to sustain extreme wind loads within an expected long lifespan.…”
Section: Wind Designmentioning
confidence: 99%